Negative correlation between IL-1 beta, IL-12 and TNF-gamma, and cortisol levels in patients with panic disorder - Fernández-Serrano, Ana Belén; Moya-Faz, Francisco José; Giner Alegria, Cesar Augusto; Fernández Rodríguez, Juan Carlos (Brain and Behavior, 2022)
Introduction Chronic exposure to stress is a major risk factor in anxiety disorders (ADs) and can be accompanied by an altered microbiome-gut-brain axis and a compromised immune system. In recent years, the study of inflammatory processes in AD has gained special attention. Continued stress causes the reactivity of the hypothalamic-pituitary-adrenal (HPA) axis, the alteration of the intestinal microbiota and the consequent release of pro-inflammatory cytokines, affecting the sensitivity to stress and the similar behavior of anxiety. Method The aim of the present study was to evaluate the interrelationships between measures of proinflammatory cytokines and cortisol in patients with panic disorder (PD). Results The main results of the correlation analysis revealed that the levels of pro-inflammatory cytokines interleukin (IL)-1 beta, IL-12, and tumor necrosis factor gamma were negatively correlated with cortisol scores (area under the curve with respect to the ground). Conclusions These results suggest that the inflammatory response is associated with the reactivity of the HPA axis in patients with PD and may influence the maintenance of anxiety behavior.
Keywords: chronic inflammatory disease; cortisol; depression; gastrointestinal symptoms; intestinal microbiota; proinflammatory cytokines; stress; JCR; Scopus